Hairy Root Cultures—A Versatile Tool With Multiple Applications - Gutierrez-Valdes, Noemi; Häkkinen, Suvi T.; Lemasson, Camille; Guillet, Marina; Oksman-Caldentey, Kirsi-Marja; Ritala, Anneli; Cardon, Florian (Frontiers in Plant Science, 2020)
Hairy roots derived from the infection of a plant by Rhizobium rhizogenes (previously referred to as Agrobacterium rhizogenes) bacteria, can be obtained from a wide variety of plants and allow the production of highly diverse molecules. Hairy roots are able to produce and secrete complex active glycoproteins from a large spectrum of organisms. They are also adequate to express plant natural biosynthesis pathways required to produce specialized metabolites and can benefit from the new genetic tools available to facilitate an optimized production of tailor-made molecules. This adaptability has positioned hairy root platforms as major biotechnological tools. Researchers and industries have contributed to their advancement, which represents new alternatives from classical systems to produce complex molecules. Now these expression systems are ready to be used by different industries like pharmaceutical, cosmetics and food sectors due to the development of fully controlled large-scale bioreactors. This review aims to describe the evolution of hairy root generation and culture methods and to highlight the possibilities offered by hairy roots in terms of feasibility and perspectives.